Leadership Competencies and Commitment to Change: The Mediating Effect of Developmental Leadership Behavior - Chee Yuet, Fanny Kho (Management Research Journal, 2017)
Leading change from the classroom is closely linked with the development of teacher leaders. It is considered to be the significant outcome of teachers’ commitment to change their ordinary role as classroom instructional leaders to school-based teacher leaders. In this regard, it is a privilege for teacher leaders to walk with principals who portray developmental leadership behavior competently. Thus, the objective of this study is to test a theory-based model predicting teachers’ leadership competencies and its relationship with principals’ developmental leadership behavior and teachers’ commitment to change. Data was collected from 928 respondents who served in 58 high performing secondary schools in Malaysia. Structural Equation Modeling was utilized to test the model developed. The results indicate that the teachers’ leadership competencies have significant relationship with principals’ developmental leadership behavior and teachers’ commitment to change. In addition, principals’ developmental leadership behavior was found to mediate the relationship between teachers’ leadership competencies and teachers’ commitment to change.